Response of peach trees to regulated deficit irrigation during stage II of fruit development and summer pruning - Lopez, G.=700 1 Arbones, A.; Del Campo, J.; Mata, M.; Vallverdu, X.
(Es, En)
Ilus., 37 ref.
Keywords: PRUNUS PERSICA; CONTENIDO DE AGUA EN EL SUELO; ESTRES; POTENCIAL HIDRICO DEL SUELO; TALLO; FRUTO; CALIDAD; ESPAÑA; CARGA DE FRUTOS; RADIACION INTERCEPTADA; SPANISH JOURNAL OF AGRICULTURAL RESEARCH